2015
DOI: 10.1186/s12971-015-0034-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of smoking reduction intervention for hardcore smokers

Abstract: BackgroundThe prevalence and correlates of hardcore smokers, who have high daily cigarette consumption, no quitting history and no intention to quit, have been studied in several western developed countries, but no previous trials of smoking cessation have tested intervention effectiveness for these smokers. The current study examined if hardcore smokers can benefit from smoking reduction intervention to achieve cessation, and explored the underlying reasons.MethodsA posteriori analysis was conducted on data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…In this study, alcohol drinking and smoking were found to be related to presenteeism. These ndings are consistent with previous studies [14,16,19,30]. The multiple logistic regression analysis from our study revealed that heavy smoking and high-risk alcohol drinking signi cantly affected presenteeism.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, alcohol drinking and smoking were found to be related to presenteeism. These ndings are consistent with previous studies [14,16,19,30]. The multiple logistic regression analysis from our study revealed that heavy smoking and high-risk alcohol drinking signi cantly affected presenteeism.…”
Section: Discussionsupporting
confidence: 93%
“…Each profile might require a different tobacco control approach [38]. Further gains in smoking cessation must focus on understanding the characteristics of 'hard-to-engage' populations [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, new strategies focused on HCS, like smoking reduction then cessation, appear effective to help hard core smokers to quit and reduce smoking [39] which is one more argument for encouraging HCS to try to quit smoking.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the very brief reduction intervention might be the critical element here, and that subsequent telephone counselling calls did not add greatly. Finally, very few of our participants were 'hardcore' smokers, which might partly explain the high reduction and quit rates [22]. Moreover, 15-20% of the participants in the control group had reduced their cigarette consumption.…”
Section: Discussionmentioning
confidence: 79%
“…While the rates in different participants under different settings may not be comparable, our high rates might be attributed to the efficacy of our intervention. Finally, very few of our participants were 'hardcore' smokers, which might partly explain the high reduction and quit rates [22]. Secondly, we warned at baseline and each follow-up that the current attempt to reduce was an intermediate step before complete smoking cessation.…”
Section: Discussionmentioning
confidence: 96%